Dependence on the mobile phone (Actual Problems of Psychology in Educational Institutions, 2019)
The article analyzes the dependence on gadgets. Nomophobiain the modern world and this dependence at different age stages have beeninvestigated. Definitely the main causes of addiction. Found that nomophobiahave people of different ages, different sexes in approximately equal amounts.Various ways to get rid of human dependence on gadgets are described. It isconcluded that dependence on a mobile phone is a disease of the XI centurywhich progresses without knowing the boundaries and treatment is possibleonly if the person recognizes this problem, the desire to get rid of thesmartphone and concrete examples of ways to get rid of nomophobia are given.
Keywords: addiction, connection, nomophobia, smartphone, social network, fear, phobia and other